2018
DOI: 10.12659/aot.907930
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Status of Children Born to Female Liver Recipients

Abstract: BackgroundImmunosuppressive treatment in pregnant organ recipients can affect functions of the fetal and newborn immune system. The aim of this study was to evaluate the effect of this treatment on selected parameters of the immune system of children born to mothers after liver transplantation.Material/MethodsThe study included 52 children born to liver recipients and 52 children in the control group. The study was conducted in the 1st Department of Obstetrics and Gynecology, Medical University of Warsaw. Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In neonates, infants, and children older than 1 year, in utero exposure to tacrolimus, cyclosporin, glucocorticoids, and/or azathioprine for maternal transplantation was not shown to result in significant changes in the serum abundance of immunoglobulins, barring higher IgA in mothers treated with cyclosporin as opposed to tacrolimus, and lower IgG1 and IgG3 in cyclosporin-exposed infants as opposed to healthy controls. 126 , 127 T cell proportions and B cell subtype populations were comparable to controls; however, in relevant studies, CD45RA+RO- naïve T cells were increased in cyclosporin-exposed children aged from newborn to 10 years of age, whereas CD45RA-RO+ memory T cells were more numerous in azathioprine-exposed children, suggesting delayed T cell maturation for cyclosporin, and accelerated T cell maturation for azathioprine. 126 , 127 , 131 In another study assessing cyclosporin-exposed infants over the first year of life, CD25 expression on T cells and CD5 expression on B cells did not increment over time, and B (including Bregs) and Treg numbers were decreased at birth.…”
Section: Effects Of In Utero Exposure To Maternal Immunosuppression I...mentioning
confidence: 82%
See 3 more Smart Citations
“…In neonates, infants, and children older than 1 year, in utero exposure to tacrolimus, cyclosporin, glucocorticoids, and/or azathioprine for maternal transplantation was not shown to result in significant changes in the serum abundance of immunoglobulins, barring higher IgA in mothers treated with cyclosporin as opposed to tacrolimus, and lower IgG1 and IgG3 in cyclosporin-exposed infants as opposed to healthy controls. 126 , 127 T cell proportions and B cell subtype populations were comparable to controls; however, in relevant studies, CD45RA+RO- naïve T cells were increased in cyclosporin-exposed children aged from newborn to 10 years of age, whereas CD45RA-RO+ memory T cells were more numerous in azathioprine-exposed children, suggesting delayed T cell maturation for cyclosporin, and accelerated T cell maturation for azathioprine. 126 , 127 , 131 In another study assessing cyclosporin-exposed infants over the first year of life, CD25 expression on T cells and CD5 expression on B cells did not increment over time, and B (including Bregs) and Treg numbers were decreased at birth.…”
Section: Effects Of In Utero Exposure To Maternal Immunosuppression I...mentioning
confidence: 82%
“… 126 , 127 T cell proportions and B cell subtype populations were comparable to controls; however, in relevant studies, CD45RA+RO- naïve T cells were increased in cyclosporin-exposed children aged from newborn to 10 years of age, whereas CD45RA-RO+ memory T cells were more numerous in azathioprine-exposed children, suggesting delayed T cell maturation for cyclosporin, and accelerated T cell maturation for azathioprine. 126 , 127 , 131 In another study assessing cyclosporin-exposed infants over the first year of life, CD25 expression on T cells and CD5 expression on B cells did not increment over time, and B (including Bregs) and Treg numbers were decreased at birth. 127 The clinical significance of these abnormalities appeared to be minimal, with no increases in immunodeficiencies or autoimmune disorders reported in the included infants.…”
Section: Effects Of In Utero Exposure To Maternal Immunosuppression I...mentioning
confidence: 82%
See 2 more Smart Citations
“…66 Drozdowska-Szymczak et al observed no significant differences in immunoglobulin concentrations at birth between infants born to mothers on Tac treatment after SOT and those born to healthy mothers. 67,68 Kociszewska-Najman et al 69 reported that white blood cell counts within the first 72 hours after birth were within the normal limits.…”
Section: Immunological Outcomesmentioning
confidence: 99%